Ductility and performance assessment of high strength self compacting concrete (HSSCC) deep beams: an experimental investigation - Mohammadhassani, M.; Jumaat, Mohd Zamin; Jameel, M.; Badiee, H.; Arumugam, A.M.S. (Nuclear Engineering and Design, 2012)
The behavior of deep beams is significantly different from that of normal beams. Because of their proportions, deep beams are likely to have strength controlled by shear. This paper discusses the results of eight simply supported high strength self compacting concrete (HSSCC) deep beams having variation in ratio of web reinforcement and tensile reinforcement. The deflection at two points along the beam length, web strains, tensile bars strains and the strain at concrete surface are recorded. The results show that the strain distribution at the section height of mid span is nonlinear. Ductility decreased with increase in tensile reinforcement ratio. The effect of width of load point and the support point is more important than the effect of tensile reinforcement ratio in preventing premature failure. Load-deflection graphs confirm linear relationship up to 85 of the ultimate load for HSSCC over-reinforcement web sections. The absorbed energy index increases with the increase in tensile reinforcement ratios.